2003
DOI: 10.1074/jbc.m305062200
|View full text |Cite
|
Sign up to set email alerts
|

An N-terminal Segment of the Active Component of the Bacterial Genotoxin Cytolethal Distending Toxin B (CDTB) Directs CDTB into the Nucleus

Abstract: Cytolethal distending toxin (CDT), produced by Actinobacillus actinomycetemcomitans, is a putative virulence factor in the pathogenesis of periodontal diseases. It is a cell cycle specific inhibitor at the G 2 /M transition. CDTB, one of the subunits of the CDT holotoxin, is implicated in a genotoxic role after entering the target cells, whereby chromosomal damage induces checkpoint phosphorylation cascades. CDTB microinjected into the cytoplasm was shown to localize in the nucleus and induce chromatin collaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 42 publications
5
84
1
Order By: Relevance
“…Mutants of CdtB lacking DNase activity fail to induce cell cycle arrest (Elwell & Dreyfus, 2000;Lara-Tejero & Galan, 2000;Nesic et al, 2004). The presence of a nuclear localization signal in the A. actinomycetemcomitans CdtB protein also supports the hypothesis that DNA is the molecular target (Nishikubo et al, 2003). This evidence, as well as the proven nuclear localization of CdtB (McSweeney & Dreyfus, 2004), firmly establishes that DNA breakage as a result of CdtB activity, and not some…”
Section: Discussionsupporting
confidence: 62%
“…Mutants of CdtB lacking DNase activity fail to induce cell cycle arrest (Elwell & Dreyfus, 2000;Lara-Tejero & Galan, 2000;Nesic et al, 2004). The presence of a nuclear localization signal in the A. actinomycetemcomitans CdtB protein also supports the hypothesis that DNA is the molecular target (Nishikubo et al, 2003). This evidence, as well as the proven nuclear localization of CdtB (McSweeney & Dreyfus, 2004), firmly establishes that DNA breakage as a result of CdtB activity, and not some…”
Section: Discussionsupporting
confidence: 62%
“…3 Nishikubo et al, 2003). An N-terminal NLS has been proposed for AactCdtB, while two C-terminal NLSs have been found in EcolCdtB-II (McSweeney & Dreyfus, 2004;Nishikubo et al, 2003).…”
Section: Cdtmentioning
confidence: 99%
“…3 Nishikubo et al, 2003). An N-terminal NLS has been proposed for AactCdtB, while two C-terminal NLSs have been found in EcolCdtB-II (McSweeney & Dreyfus, 2004;Nishikubo et al, 2003). On the basis of highly conserved N-terminal amino acid sequences corresponding to the putative NLS of AactCdtB among all known bacterial CdtB orthologues, a modular structure consisting of an Nterminal domain responsible for nuclear transport and a C-terminal DNase-like domain capable of exerting DSBs has been proposed (McSweeney & Dreyfus, 2004;Nishikubo et al, 2003).…”
Section: Cdtmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, EcCdtB has smaller clusters (one or two) of Arg/Lys residues than the classical monopartite and bipartite importin-␣ consensus sequences with two to four adjacent Arg/Lys residues (40). It should be noted that in vivo studies of AaCdtB reported an N-terminal region (Asn 48 -Ser 124 ) as the site for an NLS, although no candidate Arg/Lys residues were found in this region (47). A second tandem arginine sequence (Arg 235 -Arg 236 ) in EcCdtB, which is required for cellular entry or cytoplasmic trafficking but is not absolutely required for nuclear localization, is located in the putative EcCdtB-EcCdtC interface (12).…”
Section: Distinct Eccdtb Solution and Crystal States Provide Insightsmentioning
confidence: 99%